Mobile blended learning environment for architectural history education: students’ learning experience via mobile learning platform - Kassim, Mohd Hisyammudin; Abdullah, Fadzidah; Abdul Razak, Mohd Raziff (2017)
Architectural history education consists of a complex structure of narrative information and disseminates in the sequentces manners. This narrative information covers not only the morphological of the building but also involves various fields. leads to the learning problemsIt a huge mistake when the educationists disseminate the narrative information in the form of a textbook or written in the short form for the students to learn. Consequently, isit triggersforces the higher education institution to adopt a new innovative way of teaching and learning which parallel to the student learning trends. With the advancement of educational technology has inspired educationist to explore its potential toward learning environment. Today, the blended learning become the buzz word at the higher education institution. Thus, the research explores the Mobile Blended Learning Environment (MBLE) designed explicitly for architectural history education via the mobile platform. This mobile learning platform integrates with the mobile web, Mobile Augmented Reality (MAR) app, the online game app as well as cloud database to support various student learning activities. The research has two following objectives; First, to develop the MBLE parallel to the student learning trends at the higher education institution. Second, to evaluate the MBLE toward learning experience at the higher education institution. The research applied mix mode research where involves qualitative (exploratory reviews, expert interviews, video observation and document analysis method) and quantitative questionnaire). The reflection offers a new way of students learning environment by enhancing the traditional learning method via MBLE.